I guess ur just gunna have to bear with whatever until we have a multiple choice answer selection.
Step-by-step explanation:
Using the properties of logarithms, the left side of the equation becomes
![\log{3x^3} - \log{x^2} = \log{3x}](https://tex.z-dn.net/?f=%5Clog%7B3x%5E3%7D%20-%20%5Clog%7Bx%5E2%7D%20%3D%20%5Clog%7B3x%7D)
while the right hand side becomes
![\log{27} - \log{x} = \log{\frac{27}{x}}](https://tex.z-dn.net/?f=%5Clog%7B27%7D%20-%20%5Clog%7Bx%7D%20%3D%20%5Clog%7B%5Cfrac%7B27%7D%7Bx%7D%7D)
so we end up with
![3x^2 =27 \Rightarrow x = 3](https://tex.z-dn.net/?f=3x%5E2%20%3D27%20%5CRightarrow%20%20x%20%3D%203)
Answer:
1
Step-by-step explanation:
Here f(x) = x^2 - 2x - 5, which at x - -5 is 25 +10 - 5 = 30 and at x = 6 is 19.
The average value of a function f(x) over an interval [a, b] is
f(b) - f(a)
ave. val. = ---------------
b - a
which in this particular case is
19 - 30
ave. val. = ----------------- = -11/11 = 1
6 - (-5)
The average value of this function f(x) = x^2 - 2x - 5 on [-5, 6] is 1.
Answer:
16x^2 + 9x^2 + 9x + 13.
Step-by-step explanation:
6x^3 + 8x^2 – 2x + 4 +10x^3 + x^2 + 11x + 9
Bringing like terms together:
= 6x^3 + 10x^3 + 8x^2 + x^2 - 2x + 11x + 4 + 9
= 16x^2 + 9x^2 + 9x + 13. (answer).